Foraminiferal geochemistry and assemblage data, and pore water oxygen data of IODP Site 347-M0059 - Ni, Sha; Groeneveld, Jeroen; Fanget, Anne-Sophie; Böttcher, Michael Ernst; Liu, Bo; Lipka, Marko; Knudsen, Karen Luise; Naeraa, Tomas; Seidenkrantz, Marit-Solveig; Filipsson, Helena L (PANGAEA, 2020)
The dataset includes foraminiferal geochemistry and assemblage data, and pore water oxygen isotopes. The samples were collected during IODP Expedition 347 from Site M0059, located in the southern section of the Little Belt in the Baltic Sea. We have measured trace element concentrations (by LA-ICP-MS), oxygen and carbon isotopes of foraminiferal calcite, and fauna assemblage, for reconstruction of past environmental conditions over the past ~7.5 thousand years. We have also measured pore water oxygen isotopes from the same site. In the dataset we also present the trace element concentrations of foraminiferal calcite from IODP347 Site M0059 measured by solution-based ICP-OES. In addition, we include the measurement of water column salinity and oxygen isotopes data from cruise MSM 50 between the Skagerrak and the southern Baltic Sea.
Keywords: Foraminifera; Foraminifera; Holocene Thermal Maximum; LA-ICP-MS; NAO; Skagerrak; Stable isotopes; trace elements